2018
DOI: 10.3389/fpls.2018.00142
|View full text |Cite
|
Sign up to set email alerts
|

The Hemiparasitic Plant Phtheirospermum (Orobanchaceae) Is Polyphyletic and Contains Cryptic Species in the Hengduan Mountains of Southwest China

Abstract: Phtheirospermum (Orobanchaceae), a hemiparasitic genus of Eastern Asia, is characterized by having long and viscous glandular hairs on stems and leaves. Despite this unifying character, previous phylogenetic analyses indicate that Phtheirospermum is polyphyletic, with Phtheirospermum japonicum allied with tribe Pedicularideae and members of the Ph. tenuisectum complex allied with members of tribe Rhinantheae. However, no analyses to date have included broad phylogenetic sampling necessary to test the monophyly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 83 publications
3
48
1
Order By: Relevance
“…The more recent study by Yu & al. () highlighted the same polyphyletic issue as Dong & al. () but did not follow the taxonomy proposed in Pinto‐Carrasco & al.…”
Section: Lamialesmentioning
confidence: 62%
See 3 more Smart Citations
“…The more recent study by Yu & al. () highlighted the same polyphyletic issue as Dong & al. () but did not follow the taxonomy proposed in Pinto‐Carrasco & al.…”
Section: Lamialesmentioning
confidence: 62%
“…In that chapter, the phylogenetic relationships of the various clades in the family were discussed, and five disconnected phylogenetic trees were shown that included lists of unplaced taxa based on their assumed affinity. Although there have been numerous phylogenetic studies since 2013 (e.g., Schneider & al., ; Uribe‐Convers & Tank, ; Fu & al., ; Pinto‐Carrasco & al., ; Gaudeul & al., ; Yu & al., ; Li & al., ), most have been focused on a particular group (tribe) within Orobanchaceae. It appears that there does not exist in the literature an attempt to incorporate all the available phylogenetic information to produce a “super tree” of Orobanchaceae.…”
Section: Lamialesmentioning
confidence: 99%
See 2 more Smart Citations
“…The species of Leucothoides have their center of diversity in the Himalaya and Hengduan Mountains in East Asia, and the latter in the Andes of South America. These regions are recognized as 'species pump' areas (Terborgh 1992, Jetz et al 2004, with highly variable environmental parameters involving area, elevation, topography and climate (Körner 2004, Tang et al 2006, Schwery et al 2015, Yu et al 2018) promoting hybridization and subsequent (allo)polyploid speciation (Rauscher 2002, Nie et al 2005, Schmidt-Lebuhn et al 2010.…”
Section: Discussionmentioning
confidence: 99%